تشكل خطاب السجون بين الحرية و الإبداع رواية ياصاحبي السجن لأيمن العتوم أنموذجا دراسة جمالية - عبد اللاوي, بعطوط, نور الهدى سحر (Univercty of Eloued, 2020)
تهدف المذكرة إلى دراسة الخطاب الروائي وجمالياته في رواية "يا صاحبي السجن" لأيمن العتوم من خلال معالجة موضوعات وفيه العتبات، الفضاء المكاني، التناص. و ،الجمالية في أدب السجون مثل الجمالي للإيديولوجيا وعلاقتها ببنية الشكل ّ الكشف عن الت الروائي ولغة خطابه. وقد استبطن العنوان "يا صاحبي السجن" جماليات عدة من تناص مع القرآن الكريم ودلالة عن المكان والرفقة، وارتباطه الوثيق بعناوين فصول الرواية ومدلولاتها النصية. كما تضمن الغلاف شعرية كامنة في الصورة ورمزية ألوانها وتأويلاتها، نهاية باسم المؤلف وعتبة التجنيس، وقد كان للفضاء المكاني موضعه من الدراسة والتحليل، ضمن نطاقين داخل السجن وخارجه. وأما ، شعرية التناص وجمالياته، فقد برز من خلال التناص الديني والتناص ً وحديثا بالإضافة إلى التناص الأسطوري ً مع الشعر العربي قديما وكذا التناص مع الأمثال الشعبية. ْ وبرزتعلاقة البطل السياسي بالسلطة علىثنائية المثقف والجلاد والرفض والتمرد، ًمرتكزة ً بينةُ م أزمة المثقف المتمثلة في هاجس الاغتراب والذات المتأزمة. وقد كان للتوجهات الأيديولوجية في رواية ًأثرا لات خطاب ُتمفص "يا صاحبي السجن"، بالإضافة إلى تجليات الألم والأمل ومواطن الحرية والإبداع والتي أسهمت في تشكيل الخطاب الروائي. The research paper aims to study the narrative discourse and its aesthetics in the novel "Hey prisoners" by Ayman Al-Atoum by addressing the aesthetic issues in prison literature, including thresholds, spatial space, intertextuality , and revealing the aesthetic representation of ideology and its relationship to the structure of the narrative form and the language of his speech. The title "Hey presoners""Ya sahibay elsijn" included several aesthetics, including intertextuality with the Holly Qur’an, an indication of place and companionship, and its close connection with the titles of the chapters of the novel and their textual implications. The cover also included a poetic inherent in the image and the symbolism of its colors and interpretations, ending with the name of the author and the naturalization threshold, and the spatial space had its place of study and analysis, within two bands inside and outside the prison. As for the poetry of intertextuality and its aesthetics, it emerged through religious intertextuality and intertextuality with Arabic poetry, in the past and in the modern, in addition to the legendary intertextuality as well as intertextuality with popular proverbs. The relationship of the political hero with power emerged based on the duality of the intellectual and the executioner, rejection and rebellion, indicating the intellectual crisis represented by the perception of alienation and the critical self. Ideological trends had an impact on the details of the speech of the novel, "Hey Prisoners", in addition to the manifestations of pain, hope, and places of freedom and creativity, which contributed to the formation of the narrative discourse
Keywords: أدب السجون، العتبات، التناص، أيمن العتوم، يا صاحبي السجن; Prison literature, the thresholds, intertextuality, Ayman Al-Atoum , hey prisoners